Crystal structure of 2-chloro-1-(3-ethyl-2,6-diphenylpiperidin-1-yl)ethanone - Shreevidhyaa Suressh, V. (Acta Crystallogr E Crystallogr Commun, 2015)
In the racemic title compound, C(21)H(24)ClNO, the dihedral angle between the planes of the benzene rings is 86.52 (14)° and those between the benzene rings and the piperidine ring are 61.66 (14) and 86.39 (14)°. The piperidine ring adopts a twisted boat conformation. No directional interactions could be detected in the crystal.